MEIO AMBIENTE INCLUSIVO COMO ASPECTO REVELADOR DA CIDADANIA - David , Flavia; David , Luiz (Revista Inclusiones, 2019)
This paper seeks to demonstrate that environmental protection must be among the goals of a Democratic State. It cannot be imagined that environmental protection will be set aside by a democratic and pluralistic state. If there is concern for the environment, this concept cannot be broadly launched to allow any action to be taken as inclusive and defensive of a democratically protected environment.